Facilitating learning : a metacognitive process - Lucas, Maria Rita D.; Corpuz, Brenda B. (Quezon City Lorimar Publishing, Inc, 2007)
This book on facilitating learning. A metacognitive process aims to align teacher education with the CHED- prescribed new teacher education curriculum that is reflective on the national competency- based teacher standards with the end in view of contributing to the formation of the ideal professional teacher as concretely described in the seven integrated domains of the teaching and learning process
Keywords: Cognitive learning; learning; Teaching